UJI AKTIVITAS DIURETIK EKSTRAK ETANOL UMBUT BATANG ROTAN (Calamus rotang L.) TERHADAP MENCIT PUTIH (Mus musculus) JANTAN GALUR SWISS WEBSTER - Inderiyani Inderiyani (Jurnal Komunitas Farmasi Nasional, 2021)
Diuretics are drugs that work on the kidneys to increase the excretion of water and sodium chloride. Diuretics are used to reduce edema in congestive heart failure, some kidney diseases, hepatic cirrhosis and hypertension therapy. One of the traditional medicinal plants that is thought to have diuretic activity is rattan (Calamus rotang L.). Rattan has secondary metabolites i.e. flavonoids, alkaloids and saponins where flavonoids have biological activity as a diuretic. The purpose of this study was to determine whether the ethanol extract of rattan stem (EEUMBR) has activity as a diuretic on male white mice (Mus musculus). They are 5 groups in this study i.e. group I as a negative control (Na.CMC 0.5%), group II as a positive control (furosemide 52 mg/kg bw), group III as EEUMBR group 0.25 g/kg bw, group IV as a group. group EEUMBR 0.5 g /kg bw and group V EEUMBR group 1 g/kg bw. Data obtained by observing the volume of urine excreted for 6 hours. Data showed that the amount of urine excreted in the EEUMBR group was greater than the negative control group i.e 1.39 mL (EEUMBR 0.25 g/kg bw), 1.47 mL (EEUMBR 0.25 g/kg bw), 1.69 mL (EEUMBR 0.25 g/kg bw) while the negative control group was 1.12 mL. The results of statistical analysis showed that the five experimental groups had significant differences with a sig value was 0.02 (p<0.05). Based on these data, it can be concluded that the ethanol extract of rattan stem umbut has activity as a diuretic.